ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022) - Perbiani, Wilna; Sartono, Sartono; Setiawan, Aris (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
This research is motivated by the problem of financial difficulties that often occur in companies. The decline inthe company's financial condition and performance can make the company experience a Financial Distresscondition which, if it occurs continuously, can result in the company experiencing bankruptcy. In order for thecompany to avoid these problems, the management and shareholders of the company are required to be able towork together in maintaining and improving company performance by implementing Corporate Governancemechanisms. A good Corporate Governance mechanism will reduce the risk of Financial Distress. This study aimsto determine the effect of Corporate Governance mechanisms and Firm Size on Financial Distress. Theindependent variables used are the Number of Board of Directors, Proportion of Independent Commissioners,Managerial Ownership, and Firm Size. This study uses secondary data with a population of all BUMN companieslisted on the Indonesia Stock Exchange (BEI) in 2019-2022. The sampling technique used purposive sampling byobtaining a sample of 11 companies. The data analysis technique used is descriptive statistics, classicalassumption test and hypothesis testing. The results in this study indicate that the Number of Boards of Directors,Proportion of Independent Commissioners, and Managerial Ownership have a significant negative effect onFinancial Distress while Firm Size has no effect on Financial Distress .